2021
DOI: 10.3389/fevo.2021.636804
|View full text |Cite
|
Sign up to set email alerts
|

Light Intensity Influence on Growth and Photosynthetic Characteristics of Horsfieldia hainanensis

Abstract: Due to both anthropogenic and natural causes, the number of Horsfieldia hainanensis has been decreasing each year in the Tongza Branch nursery (109.534 525°E, 18.763 516°N) of the Hainan Academy of Forestry, China. Consequently, the protection of H. hainanensis is urgent, as is that of most rare tree species. To develop a more comprehensive understanding of the H. hainanensis growth environment, we took 3-year-old H. hainanensis saplings as the research object. We controlled the light intensity by setting diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…Transpiration acts as a driving force behind the absorption and transportation of water and inorganic irons to the above-ground part of the plant [43]. Additionally, loss of water through the stomata is an important heat dissipation mechanism [37]. We found that under optimum light conditions (L400 and L500), the P n , T r and g s of alfalfa can be increased and the C i reduced, which in turn enhanced photosynthesis in alfalfa plants.…”
Section: Effect Of Light Intensity On Photosynthetic Characteristics ...mentioning
confidence: 76%
See 1 more Smart Citation
“…Transpiration acts as a driving force behind the absorption and transportation of water and inorganic irons to the above-ground part of the plant [43]. Additionally, loss of water through the stomata is an important heat dissipation mechanism [37]. We found that under optimum light conditions (L400 and L500), the P n , T r and g s of alfalfa can be increased and the C i reduced, which in turn enhanced photosynthesis in alfalfa plants.…”
Section: Effect Of Light Intensity On Photosynthetic Characteristics ...mentioning
confidence: 76%
“…The chlorophyll content of leaves of maize (Zea mays) plants grown in low light intensity was significantly higher than that of leaves grown in high light [36], which agrees with our results. Increased Chl b content could be a typical response to low-light conditions that allows shade-intolerant plants to capture more photosynthetically efficient blue light, thereby stimulating adaptive photomorphogenesis and alleviating the negative impacts of shade stress on photosynthetic activities [37]. Yi et al (2020) [38] also found that adequate CO 2 assimilation and fixation promoted sugar accumulation and decreased pigment-protein complexes in leaves in high light intensity, resulting in senescence and chlorophyll degradation.…”
Section: Effect Of Light Intensity On Chlorophyll Content and Chlorop...mentioning
confidence: 99%
“…Light intensity is an important factor for plant growth. Growth and yield productivity including fresh weight and dry weight of plants are significantly affected by an increase in light intensity [32]. This condition is supported by plant photosynthesis which takes place optimally under sufficient light conditions at opened area of monoculture plot.…”
Section: The Biomass Of Arrowroot and Cardamommentioning
confidence: 99%
“…The behaviour of all life forms is defined as coordinated responses such as actions or inactions to an internal or external stimulus Changes in light intensity leads to considerable changes in the spatial orientation patterns. For example, exposure to high intensity tends to reverse the natural lunar-guided foraging patterns, which decrease during brighter moonlight in naturally lit conditions and increase when exposed to high intensity ALAN (5); similarly, slight increase or decrease in light intensity leads to considerable changes in leaf morphology (78), and compared to high intensity light, reduced light intensity can increase the net nutrition rate of plants (79). Spatial heterogeneity in light intensity is also recommended to support the life-sustaining behaviours of certain life forms (67,80).…”
Section: Classifying the Life-sustaining Behaviours Within Lighted En...mentioning
confidence: 99%